Maximizing Returns: The Impact of Key Ratios on Bank Mega Syariah's ROA - Najib, Intan Permatasari; Ajuna, Luqmanul Hakiem; Rusdi, Wahyudi; Kadim, Immawan Muhajir (Journal of Principles Management and Business, 2024)
This study investigates the factors influencing Return on Assets (ROA) at PT. Bank Mega Syariah, focusing on Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Costs to Operating Income (BOPO). The research utilizes quarterly financial reports from PT. Bank Mega Syariah for the 2016–2023 period and applies a quantitative research approach. Data analysis includes classical assumption testing, multiple linear regression analysis, and hypothesis testing. The classical assumption test confirms that the data meets the requirements for multiple linear regression modeling. The hypothesis testing reveals that NPF has a significant positive effect on ROA, with a p-value of 0.007 (< 0.05) and a t-value of 2.894. Conversely, FDR, with a p-value of 0.308 (> 0.05) and a t-value of 1.038, shows no significant effect on ROA despite its positive direction. BOPO demonstrates a significant negative effect on ROA, with a p-value of 0.000 (< 0.05) and a t-value of -5.374. Additionally, the F-test results indicate a significant simultaneous effect of NPF, FDR, and BOPO on ROA, with a p-value of 0.000 (< 0.05). These findings highlight the importance of efficient cost management and asset quality in enhancing profitability, while FDR requires further exploration for its potential role in financial performance.